Flood Susceptibility in Urban Environments: Analysis of the Ribeirão Lageado Basin Based on the HAND Model - Oliveira, Matheus Vargas de; Piroli, Edson Luís (Scientific Journal ANAP, 2025)
Objective - To analyze flood susceptibility in the Ribeirão Lageado Basin, located in the municipality of Avaré-SP, in order to support planning and environmental management actions in built-up areas. Methodology - Application of the HAND model (Height Above Nearest Drainage), a topographic tool used to estimate surface runoff potential based on the relative elevation to the nearest drainage. Digital Elevation Model (DEM) data were used and integrated into a Geographic Information System (GIS). Originality / Relevance - The study stands out by applying the HAND model in a medium-sized urban basin, contributing to discussions on hydrological risks associated with unplanned urbanization. Results - Approximately 10% of the basin shows high or very high flood susceptibility, especially in densely built-up areas lacking vegetation cover. Theoretical and methodological contributions - Validation of the HAND model as an effective tool for territorial management and rapid, accessible diagnostics of urban risk. Reinforcement of the integration between spatial analysis and territorial planning. Social and environmental contributions - Highlights the need for public policies aimed at responsible land use and flood risk mitigation in vulnerable urban areas.